2022
DOI: 10.1007/jhep08(2022)242
|View full text |Cite
|
Sign up to set email alerts
|

$$ \mathcal{N} $$ = 1 S-fold spectroscopy

Abstract: We analyse the spectrum of Kaluza-Klein excitations above three distinct families of $$ \mathcal{N} $$ N = 1 AdS4 solutions of type IIB supergravity of typically non-geometric, S-fold type that have been recently found. For all three families, we provide the complete algebraic structure of their spectra, including the content of OSp(4|1) multiplets at all Kaluza-Klein levels and their charges under the residual symmetry groups. We also provide extensive results for the multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Only for these conjugacy classes it is possible to compactify on a circle with duality monodromy. This has been recently used in lower-dimensional compactifications to produce new IIB backgrounds and associated dual CFT's [69][70][71][72][73], but in nine dimensions these monodromies do not preserve any supercharges [19,21]. Therefore, we now move to monodromies with det h = −1.…”
Section: 19)mentioning
confidence: 99%
“…Only for these conjugacy classes it is possible to compactify on a circle with duality monodromy. This has been recently used in lower-dimensional compactifications to produce new IIB backgrounds and associated dual CFT's [69][70][71][72][73], but in nine dimensions these monodromies do not preserve any supercharges [19,21]. Therefore, we now move to monodromies with det h = −1.…”
Section: 19)mentioning
confidence: 99%
“…This, in particular, includes vacua with little or no (super-)symmetry, and has yielded interesting insights. For example, the recent work on KK spectra has revealed that there infinitely-many unprotected operators whose conformal dimensions are finite even at strong coupling [11,12], that certain conformal manifolds are compact, even though this is not apparent from studying the holographic duals JHEP05(2024)214 within a consistent truncation [13][14][15][16], that non-supersymmetric AdS vacua that are stable within a consistent truncation can nonetheless be perturbatively unstable due to higher KK modes that do not form part of the consistent truncation [17], and that there are several examples of isolated and continuous families of non-supersymmetric AdS vacua that are perturbatively stable within the full 10-dimensional supergravity [14,[18][19][20][21].…”
Section: Jhep05(2024)214mentioning
confidence: 99%
“…These techniques, for the first time, have given access fo the full Kaluza-Klein spectrum for warped compactifications with few or no remaining (super-)symmetries [3,4,[6][7][8][9][10][11][12][13][14][15] and led to many interesting insights. For supersymmetric AdS vacua, the protected part of the Kaluza-Klein spectrum can be matched with the superconformal index of the CFT, as was done for the Pilch-Warner AdS 5 vacuum in [10] and for the SU(3) × U(1)-invariant AdS 4 vacuum in N = 8 SUGRA in [4,16].…”
Section: Introductionmentioning
confidence: 99%
“…For supersymmetric AdS vacua, the protected part of the Kaluza-Klein spectrum can be matched with the superconformal index of the CFT, as was done for the Pilch-Warner AdS 5 vacuum in [10] and for the SU(3) × U(1)-invariant AdS 4 vacuum in N = 8 SUGRA in [4,16]. Moreover, the Kaluza-Klein spectrum can be used to determine compactness of the conformal manifold, which may not be visible in the consistent truncation [14,15], see also [17]. For non-supersymmetric vacua that are perturbatively stable within the consistent truncation, [6] showed that instabilities can be nonetheless triggered from higher Kaluza-Klein modes.…”
Section: Introductionmentioning
confidence: 99%